Validation of project management information systems for industrial construction projects. Issue 5 (3rd September 2022) - Choi, Jaehyun; Ha, Minhui
ABSTRACT: Project Management Information Systems (PMIS) have been widely used for effective construction project management especially for EPC (Engineering, Procurement, and Construction) projects. It saves a significant amount of time and effort, making project management tasks more effective and efficient. However, most Korean EPC firms develop and use PMIS without validating the system's compliance with global project management standards. This research presented a methodology to validate the composition and functions of PMIS to ensure it conforms to the global project management standards of project management practice. The researchers defined the core and sub-management processes as well as the required capability level. Proposed global practice, which serves as evaluation criteria, was developed in the form of a work process. Sample PMIS evaluation results confirmed that the core management processes and their functions are compliant with overall global practice. The proposed work processes and evaluation criteria can serve as a global project management requirement for developing PMIS in the future.